The Playful Citizen - Glas, René; Lammes, Sybille; Lange, Michiel; Raessens, Joost; Vries, Imar (Amsterdam University Press, 2019)
This edited volume collects current research by academics and practitioners on playful citizen participation through digital media technologies.